2017
DOI: 10.1038/nature22312
|View full text |Cite
|
Sign up to set email alerts
|

Human pluripotent stem cells recurrently acquire and expand dominant negative P53 mutations

Abstract: Human pluripotent stem cells (hPSCs) can self-renew indefinitely, making them an attractive source for regenerative therapies. This expansion potential has been linked with acquisition of large copy number variants (CNVs) that provide mutant cells with a growth advantage in culture1–3. However, the nature, extent, and functional impact of other acquired genome sequence mutations in cultured hPSCs is not known. Here, we sequenced the protein-coding genes (exomes) of 140 independent human embryonic stem cell (hE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
391
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 429 publications
(418 citation statements)
references
References 45 publications
13
391
0
3
Order By: Relevance
“…The most proliferative individuals outcompete populations of single cell organisms, while multicellular organisms require cellular cooperation, at the expense of competition, to maintain coordinated, specialized functions. The need for cooperation starts in embryonic development, where p53 restricts expansion of individual “cheater” cells, observed in chimeric blastocysts upon p53 knockdown (Dejosez et al, 2013) and following positive selection of spontaneous TP53 mutations detected in commonly used human ES lines (Merkle et al, 2017). Tight regulation of DNA methylation by DNMT and TET family enzymes requires p53 and it appears that epigenetic disorder contributes to this clonal heterogeneity in p53-deficient ESC colonies (Tovy et al, 2017).…”
Section: The Origins Of P53mentioning
confidence: 99%
“…The most proliferative individuals outcompete populations of single cell organisms, while multicellular organisms require cellular cooperation, at the expense of competition, to maintain coordinated, specialized functions. The need for cooperation starts in embryonic development, where p53 restricts expansion of individual “cheater” cells, observed in chimeric blastocysts upon p53 knockdown (Dejosez et al, 2013) and following positive selection of spontaneous TP53 mutations detected in commonly used human ES lines (Merkle et al, 2017). Tight regulation of DNA methylation by DNMT and TET family enzymes requires p53 and it appears that epigenetic disorder contributes to this clonal heterogeneity in p53-deficient ESC colonies (Tovy et al, 2017).…”
Section: The Origins Of P53mentioning
confidence: 99%
“…A study utilizing this approach showed that in normal skin cells, which are often used to derive iPSCs, many cancer genes harbor somatic mutations that were likely caused by ultraviolet (UV) light exposure (Martincorena et al, 2015). Additionally, a study on human embryonic stem cells (Merkle et al, 2017) found that ~20% of analyzed cell lines had deleterious subclonal mutations, including some known cancer drivers in TP53 . We hypothesize that due to their different origins, clonal and subclonal mutations have been under different selective pressures.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations are well known for causing cancer through inheritance, environmental carcinogens or DNA replication errors (23 (24).…”
Section: Conventional Therapy Targeted Therapymentioning
confidence: 99%